Fast changeovers using AIV and a tool platform - Omosanya, Hafeez Abolade Olav (UiT Norges arktiske universitet, 2021)
Fast changeover is changing from one process or machine to another line, process, or machine to produce different products or services. Lean aims at reducing waste, improving productivity, and eliminating non-value-added activities to the customer. Whilst achieving sustained continual improvement in certain activities and process of an organization. This project focuses on implementing the methodologies used in lean to improve a manufacturing process that has a changeover, and integrate an AIV (Automated Intelligent Vehicle) with a tool platform or top module into the same process. After careful literature review and research, I was able to set up a process in the machining laboratory of ‘UiT Universitet i Norge, Narvik,’ that is of value to a customer. I identified the step with the need of a fast tool change and optimized the entire process using a software called Simul8. After running the simulation for a period of two weeks and doing some analysis for the processes, I achieved an optimal solution that ensures that all bottlenecks and buffers were eliminated. I also conducted a smooth flow of the process, improving productivity, efficiency, and reduction in changeover time.